2019
DOI: 10.1111/ijsw.12391
|View full text |Cite
|
Sign up to set email alerts
|

Changes in household poverty among South Korean young adults: Decomposition analysis for 1995, 2006 and 2016

Abstract: This study analysed the causes behind changes in the poverty rate among young South Korean households, using the 1995, 2006 and 2016 Household Income and Expenditure Survey. Labour market instability has intensified since the Asian economic crisis of 1997. This has increased the risk of poverty among young people who lack financial assets and must obtain economic security through work. The poverty rates among people aged 18–29 have steadily increased. Using Oaxaca–Blinder decomposition, this study evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Conversely, research underscores the significance of unstable housing conditions (Paolini, 2013) and parental indifference (Bynner & Parseons, 2002) as substantial contributing factors. Although studies on this topic are limited in South Korea, findings align with those reported in Western literature, emphasizing the role of lower education levels, employment instability, and precarious living arrangements as primary drivers of heightened social exclusion among youth (Byun & Lee, 2022;Y. Lee & Park, 2021).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Conversely, research underscores the significance of unstable housing conditions (Paolini, 2013) and parental indifference (Bynner & Parseons, 2002) as substantial contributing factors. Although studies on this topic are limited in South Korea, findings align with those reported in Western literature, emphasizing the role of lower education levels, employment instability, and precarious living arrangements as primary drivers of heightened social exclusion among youth (Byun & Lee, 2022;Y. Lee & Park, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…The gap between the changing patterns of youth social exclusion is said to continue because of the strong state dependence on youth income and employment categories (Y. Choi, 2018;Nam, 2021) and the insignificant decrease in the multidimensional poverty rate (Byun & Lee, 2022). This result is similar to that in H. Park and Chung's (2012) study, which examined the social exclusion of the elderly by type.…”
Section: Discussionmentioning
confidence: 68%
“…Overall, the relative poverty risk is high for young people living alone or for single-parent youth, whereas the relative poverty risk for young people living with parents, or without children but with a partner, is low. As pointed out in previous studies, living with parents seems to be a factor that lowers the risk of poverty among young people (Aassve, Davia, Iacovou, and Mazzuco, 2005;Mencarini, 2005, 2006;Aassve, Cottini, and Vitali, 2013;Groh-Samberg and Voges, 2014;Ayllón, 2015;Byun, 2020;Kim, 2010, Kim and Kim, 2013Kim et al, 2017). The poverty risk of young people living with their parents did not change significantly in other regions, but in East Asia, the poverty risk of young people living with their parents was slightly lower than in the early 2000s.…”
Section: Leaving Home and Youth Poverty In East Asiamentioning
confidence: 81%
“…Among the different forms of parental support, cohabitation with parents has been regarded as a significant factor in lowering the risk of youth poverty (Aassve, Davia, Iacovou and Mazzuco, 2005;Mencarini, 2005, 2006;Aassve, Cottini, and Vitali, 2013;Groh-Samberg and Voges, 2014;Ayllón, 2015;Byun, 2020;Kim, 2010, Kim and Kim, 2013Kim et al, 2017). This is because, by living with their parents, young people can enjoy access to a relatively stable household income as well as reduction in theircost of living by lowering or removing housing costs (Aassve, Iacovou, and Mencarini, 2006, p. 34), or by accumulating assets for future independence while staying in parental homes (Aassve, Iacovou, and Mencarini, 2006;De Marco and Berzin, 2008;Majamaa, 2011;France, 2008;Yaqub, 2002).…”
Section: Characteristics Of Youth Poverty and Familymentioning
confidence: 99%